Synergistic valuations and efficiency in spectrum auctions. (February 2018) - Goetzendorff, Andor; Bichler, Martin; Goeree, Jacob K.
Abstract: In spectrum auctions, bidders typically have synergistic values for combinations of licenses. This has been the key argument for the use of combinatorial auctions in the recent years. Considering synergistic valuations turns the allocation problem into a computationally hard optimization problem that generally cannot be approximated to a constant factor in polynomial time. Ascending auction designs such as the Simultaneous Multiple Round Auction (SMRA) and the single-stage or two-stage Combinatorial Clock Auction (CCA) can be seen as simple heuristic algorithms to solve this problem. Such heuristics do not necessarily compute the optimal solution, even if bidders are truthful. We study the average efficiency loss that can be attributed to the simplicity of the auction algorithm with different levels of synergies. Our simulations are based on realistic instances of bidder valuations we inferred from bid data from the 2014 Canadian 700 MHz auction. The goal of the paper is not to reproduce the results of the Canadian auction but rather to perform "out-of-sample" counterfactuals comparing SMRA and CCA under different synergy conditions when bidders maximize payoff in each round. With "linear" synergies, a bidder's marginal value for a license grows linearly with the total number of licenses won, while with the "extreme national" synergies, this marginal value is independent of the number of licenses won unless the bidder wins all licenses in a national package. We find that with the extreme national synergy model, the CCA is indeed more efficient than SMRA. However, for the more realistic case of linear synergies, SMRA outperforms various versions of CCA that have been implemented in the field including the one used in the Canadian 700 MHz auction. Overall, the efficiency loss of all ascending auction algorithms is small even with high synergies, which is remarkable given the simplicity of the algorithms. Highlights: We interpret auctions as heuristics to solve a computationally hard allocation problem. We analyze the average approximation ratios of ascending auction in spectrum auctions. Numerical experiments are based on data from the Canadian 700 MHz auction. The study compares different versions of the CCA and the SMRA auction formats. The average efficiency loss of simple auction algorithms is surprising low.